Place identity through plant motif on streetscapes in the Royal Town of Kuala Kangsar, Perak ,Malaysia - Intan Khasumarlina Mohd Khalid (Tanjong Malim, 2020)
Place identity through plant motif on streetscapes in the Royal Town of Kuala Kangsar, Perak ,Malaysia by Intan Khasumarlina Mohd Khalid